Problem ludzkiej wolności i adekwatnej interpretacji przyrody w świetle genocentryzmu - Anna Marek-Bieniasz (Studia Ecologiae et Bioethicae)
In the article, the stance of genetic determinism, represented by Edward Wilson and Richard Dawkins on the grounds of sociobiology, has been presented and critically commented. The stance finds the gene to be the main actor on the stage of life, whom anything else in nature, including man – seen as a machine of replicators’ survival – is subjected. The criticism of the stance held by radical sociobiologists, undertaken by the author, results among other things from her conviction of inability to reduce the meaning of human existence to being subordinated to genes’ existence.